Legal Provisions of Foreign Investment in Badung Regency - Bali - AGUNG, Anak Agung Istri; SUKANDIA, I Nyoman; SUJANA, I Nyoman (Protection: Journal Of Land And Environmental Law, 2024)
The progress of the Indonesian nation is also supported by the presence of investors who are willing to invest in important domestic sectors. Investment is one of the instruments that drives economic progress in Indonesia, especially in Badung Regency - Bali. Many foreigners come to Bali for various purposes, including vacationing while doing business, working, learning about culture, doing research, or investing. Recently, there have been many foreign business activities involving property rental (land and buildings) either by individuals or in the form of PT PMA (Limited Liability Company with Foreign Investment) in Indonesia. This study aims to determine and understand the legal provisions for foreign investment in Bali, especially in Badung Regency and legal protection for foreigners investing in Bali based on applicable provisions. The method used in this study is normative legal research to find the type of investment and legal protection for foreigners investing in Bali based on applicable provisions.